Evaluasi Kinerja Pelayanan Administrasi Kependudukan di Desa Pinang Mas Kecamatan Sungai Pinang Kabupaten Ogan Ilir - Indra Gunawan; Alamsyah Alamsyah; Mega Nugraha (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Indra Gunawan. Village government is the lowest hierarchy in the bureaucratic system in Indonesia, therefore the role of village government is very important in providing services to village communities, this is the responsibility of the village government in providing maximum service. The purpose of providing services is to fulfill the basic needs and rights of every citizen and population for an administrative service provided by the government for the public interest, one type of public service is public service in the field of population administration. However, all service activities need to be evaluated to assess and ensure that population administration services are running in accordance with the regulations and expectations of the community. In this study the authors took the title "Performance Evaluation of Population Administration Services in Pinang Mas Village, Sungai Pinang District, Ogan Ilir Regency". This type of research is a qualitative approach that emphasizes the process. This research was conducted with the aim of evaluating the performance of population administration services in Pinang Mas Village, Sungai Pinang District, Ogan Ilir Regency, as well as to find out what efforts have been made by the Pinang Mas Village Government to improve the performance of population administration services. The evaluation analysis of this study used the CIPP (Contact, Input, Process, Product) method from Daniel Stuflebean and the PDCA Cycle Method (Plan, Do, Check, Action) from Dr. W. Edwards Deming to analyze efforts to improve the performance of population administration services. The results of the study indicate that the performance of population administration services in Pinang Mas Village, Sungai Pinang District, Ogan Ilir Regency has not gone well because there are still many obstacles and obstacles encountered, for example supervision has not been carried out intensively, lack of budget, limited supporting facilities and infrastructure, not yet established standards. Operational Procedures (SOP) and low public interest in the need for population documents. While the efforts made in order to improve the performance of the Pinang Mas Village Government have not been carried out optimally, from the three main aspects of improving service performance namely, increasing the ability of Human Resources, SOP Development and Improving facilities and infrastructure, the efforts made only rely on increasing Human Resources Humans and even then are personal, have not touched the substance of the problem.